Directional properties of the loudspeaker systems with analog and digital crossover networks - NIEWIAROWICZ, Marek; ŁOPACZ, Henryk (Archives of Acoustics, 2008)
Directional properties of loudspeaker systems with analog and digital crossover networks have been investigated. The study has been performed for a three-way loudspeaker system subjectively classified as of average quality. The digital crossover networks have been designed in such manner that the cut-off frequencies of filters (1000 Hz and 5000 Hz) corresponded to those of the analog networks and the slopes of the amplitude characteristics were 12 and 18 dB/oct. The set of impulse responses for different angles in the whole sphere around the loudspeaker system were measured and then, applying a convolution with the excitation signals of the "tone burst" type, for some specific frequencies from the cut-off region of crossover networks, the directional characteristics have been calculated for the steady and transient states. The quantitative analyses of results, based on the values of directional coefficient, show significant differences between the characteristics in steady and transient states, as well as for the analog and digital systems.